Estudo da metalotioneína, óxido nítrico sintase II e óxido nítrico em neoplasia cutâneas associadas a radiação actínica - Borges Júnior, Paulo César (2004)
ABSTRACT - Chapter I Basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) are the most frequent skin cancer in Brazilian people. Its pathogeny is linked to the genetic effects of actinic radiation exposure, specially to the ultraviolet rays ranging from 290 to 320 nm wavelength. Metallothionein (MT) are low molecular weight proteins with high affinity for heavy metal, whose intracellular function is related to heavy metals and free radical detoxification. MT´s actinic aggression protective action have been showed in others studies. On the other hand, its overexpression in different kind of tumors have been related to major aggressiveness and worst prognostic. The proposal of this study was to evaluate the expression of MT in skin cancer associated to actinic radiation. Eighteen BCC cases, five SCC and six normal skin fragments were used for this purpose. To analyze, we used the streptavidin biotin peroxidase technique and anti-MT primary antibody. The results showed that in the normal skin the marking situated in the epithelium basal layer. This marking extended to suprabasal layer of exposed to sun light skin (ES), near the tumor. Six cases of BCC (33%) was absent MT immunoreactivity, while all of SCC showed strong MT immunostaining . Only one SCC case (20%) and eight BCC case (44%) showed low MT expression. However, 80% of SCC cases (4/5) had intense staining, while only 22% of BCC cases (4/18) showed the same staining pattern. The average of ID for BCC was 0,69 +- 0,48, and for SCC was 1,55 +- 0,77. The results demonstrate that MT expression is related to SCC, suggesting a closely association with aggressive tumor. ABSTRACT - Chapter II Basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) are the most frequent skin cancer in Brazilian people. They are invasive tumors and its pathogeny is linked to actinic radiation. The nitric oxide synthase induced enzyme (iNOS) is a protein responsible to produce nitric oxide (NO), whose prompt can be related to sun exposure. Your expression and consequent NO production may play a role in carcinogenesis and tumor progression. We used eighteen BCC cases, seven SCC cases and six normal skin (NS) to study iNOS expression, and sixteen BCC cases, six SCC cases and six NS fragments not exposed to sun light to study NO production. The iNOS expression was evaluated by Western Blot technique, and the NO production was dosed by nitrite and nitrate residues, obtained by using Greiss reaction. The results were statistically analyzed according to the average of the obtained values by the Student test t, with confidence interval of 95%. BCC iNOS expression was lower than NS (p = 0,029). SCC iNOS expression was higher than NS (p = 0,025) and BCC (p = 0,0001). NO production did not showed significant difference in the tumors studied. The results suggests that iNOS superexpression is associated with more aggressive skin tumors. The NO production may not be correlated with the iNOS activity. ABSTRACT - Chapter III Metallothionein (MT) is a protein with 6 to 7 kD of molecular weight which has a high affinity for heavy metal, specially zinc. It acts as a natural zinc store, and has been related to cell protection mechanism at free radical aggression. Recent founds suggests a protective role to MT to actinic aggression. The nitric oxide (NO), an important cellular metabolite, has been identified in models of actinic aggression. It s unknown if your presence acts in a protective way, signaling a oxidative stress by the higher production of free radicals or if your presence acts directly on DNA damage, producing effect directly in the carcinogenesis. An hypothetic mechanism suggests that NO may be associated with MT induction, that acts as a protector whereas your metal quelant action stimulated MT s genetic activation because of higher intracellular zinc concentration. Another mechanism that attaches the action of MT and NO could be apoptosis. In this study, we tried to identify a correlation of MT expression and NO production with iNOS in the neoplasias associated with actinic aggression. The expression of MT was evaluated immunohistochemically by using the streptavidin biotin peroxidase technique, being expressed in distribution marking index, that reflects the tumor marking percentage associated with the marking intensity. The NO in the tumor was measured indirectly with nitrite and nitrate concentrations by using Greiss technique, expressing the values in µmol. The iNOS measurement was realized using Western Blot technique, revealed by the chemo luminescence technique with the values expressed in absorbance index. The correlated analysis was performed by Spearman test. Our results showed absence of correlation among the variables. These findings suggests that the role of MT, iNOS and NO in the actinic carcinogenesis can be in a independently way.